Genome-Wide Analysis of Basic Helix-Loop-Helix Transcription Factors to Elucidate Candidate Genes Related to Fruit Ripening and Stress in Banana (Musa acuminata L. AAA Group, cv. Cavendish) - Wang, Zhuo; Jia, Caihong; Wang, Jing-Yi; Miao, Hong-Xia; Liu, Ju-Hua; Chen, Cui; Yang, Hui-Xiao; Xu, Biyu; Jin, Zhiqiang (Frontiers in Plant Science, 2020)
The basic helix-loop-helix (bHLH) proteins are a superfamily of transcription factors (TFs) that can bind to specific DNA target sites, playing a central role in a wide range of metabolic, physiological, and developmental processes in higher organisms. However, no systemic analysis of bHLH TFs has been reported in banana, a typical climacteric fruit in tropical and subtropical regions. In our study, 259 MabHLH TF genes were identified in the genome of Musa acuminata (A genome), and phylogenetic analysis indicated that these MabHLHs could be classified into 23 subfamilies with the bHLHs from rice and Arabidopsis. The amino acid sequences of the bHLH domain in all MabHLH protein sequences were quite conserved, especially Arg-12, Arg-13, Leu-23, and Leu-79. Distribution mapping results showed that 258 MabHLHs were localized on the 11 chromosomes in the Musa acuminata genome. The results indicated that 40.7% of gene duplication events were located in collinear fragments, and segmental duplications might have played a key role in the expansion of MabHLHs. Moreover, the expression profiles of MabHLHs in different fruit development and ripening stages and under various abiotic and biotic stresses were investigated using available RNA-sequencing data to obtain fruit development, ripening-specific, and stress-responsive candidate genes. Finally, a co-expression network of MabHLHs was constructed by weighted gene co-expression network analysis to elucidate the MabHLHs that might participate in important metabolic biosynthesis pathways in banana during development and the response to stress. A total of 259 MabHLHs were identified, and their sequence features, conserved domains, phylogenetic relationships, chromosomal distributions, gene duplications, expression profiles, and co-expression networks were investigated. This study systematically identified the MabHLHs in the Musa acuminata genome at the genome-wide level, providing important candidate genes for further functional analysis. These findings improve our understanding of the molecular basis of developmental and stress tolerance in an important banana cultivar.